Investigation of the Performance of Donor–Acceptor Conjugated Polymers in Electrolyte‐Gated Organic Field‐Effect Transistors. (24th June 2021) - Doumbia, Amadou; Tong, Jincheng; Wilson, Richard J.; Turner, Michael Lewis
Abstract: Electrolyte‐gated organic field‐effect transistors (EGOFETs) are gaining interest for application in bioelectronic devices. However, robust performance in terms of charge‐carrier mobility, on‐to‐off drain current ratio ( I on / I off ), and turn‐on speed are required for real application. Here, donor‐acceptor (D‐A) conjugated polymers, namely poly[2, 5‐(2‐octyldodecyl)‐3, 6‐diketopyrrolopyrrole‐alt‐5, 5‐(2, 5‐di(thien‐2‐yl)thieno[3, 2‐b]thiophene)] (PDPPDTT) and indacenodithiophene‐co‐benzothiadiazole (PIDTBT), are evaluated in EGOFETs. The operational performance of these materials is compared to that of the well‐established conjugated polymer, poly[2, 5‐bis(3‐hexadecylthiophen‐2‐yl)thieno[3, 2‐b]thiophene] (PBTTT). The effective mobility extracted for the PDPPDTT (0.18 cm 2 V −1 s −1 ), and PIDTBT (0.16 cm 2 V −1 s −1 ) devices is almost double that of the PBTTT (0.10 cm 2 V −1 s −1 ) based device and the I on / I off is one ((PDPPDTT): 3 × 10 3 ) or two ((PIDTBT): 2 × 10 4 ) orders of magnitude higher than that of PBTTT (2 × 10 2 ) devices. The extracted values compare favorably to those of the highest performing EGOFETs and EGOFETs based on the D‐A polymers turn from off to on state two to ten times faster than the analogous PBTTT device with an improved subthreshold swing. These results show that D‐A polymers with a planar conjugated backbone enable the development of robust EGOFETs that are well appropriate for applications in bioelectronic devices. Abstract : Conjugated polymers with donor‐acceptor groups incorporated into the backbone (PDPPDTT and PIDTBT) have been used as the semiconducting layer in electrolyte gated organic field effect transistors. These polymers show excellent, reproducible performance with high on‐off ratios and rapid turn on suitable for use as bioelectronic devices.